Job analysis of Ex-Officio Head of Batam Indonesia Free Zone Authority (BP Batam): Relationship between Performance and Political Relation - Muzwardi, Ady (Jurnal Magister Administrasi Publik, 2021)
On 27 September 2019, the Mayor of Batam officially became the ex officio Head of Batam Indonesia Free Zone Authority (BP Batam). The ex-officio term of the Head of BP Batam is the same as the term of office of the Mayor of Batam. The ex-officio position of the Head of BP. Batam is a new position in Indonesia. This position combines a political position, namely the mayor of Batam with a professional position in the Concession Board. ex-officio Head of BP Batam was formed as a means to reduce the conflict of leadership dualism in Batam City. The ex-officio position of the Head of BP Batam spans political relations that are full of interests so that potential obstacles in developing performance can occur. This study aims to analyze the ex-officio performance of the Head of BP Batam and analyze the political relations in the ex-officio position of the Head of BP Batam and see its performance in the first year during the covid 19 pandemics. This study uses a qualitative method. Data collection techniques in this study used documentation studies and field studies. The results of this study explain that the ex.officio leadership function of the Head of BP Batam in the early years has gone according to plan, although there are some.